Recent Decreasing Trends in Surface PM2.5 over East Asia in the Winter-Spring Season: Different Responses to Emissions and Meteorology between Upwind and Downwind Regions - Young-Hee Ryu; Seung-Ki Min; Alma Hodzic (Aerosol and Air Quality Research)
Abstract This study developed and evaluated a WRF-Chem modeling system that reflects the effect of recent emission regulations on the PM2.5 above East Asia by utilizing an updated anthropogenic emission inventory for 2013–2018. This system accurately reproduced the monthly means, daily variations, and vertical profiles of PM2.5 during winter and spring over the Seoul Metropolitan Area (SMA) in South Korea and the North China Plain (NCP) and Yangtze River Delta (YRD) in China. Furthermore, it demonstrated that the decline in PM2.5 over the latter nation is attributable to control measures in China that have been in effect since 2013. The most polluted of the three target regions, the NCP, which is also upwind (in contrast to the downwind YRD and SMA), exhibited the largest decrease due to emission reduction. For example, the simulated mean PM2.5 concentration for February dropped by 39% over the NCP but by merely 17% over the YRD between 2013 and 2018. Additionally, the SMA displayed only minor changes in the concentration during winter and a weak decreasing trend during spring. In addition to emission reduction, meteorology significantly modulated the level of PM2.5; it produced larger interannual variations in the downwind regions than the upwind one, accounting for changes in concentration as high as 35% and 45% in the SMA during winter and spring, respectively, versus 11% and 12% in the NCP. Finally, the downwind regions also showed more complex behaviors for the secondary aerosols, which did not always follow the decreasing trends of their precursors.